2002
DOI: 10.1021/jo025758a
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Molecular Folding and Supramolecular Structures of Triptycene-Derived Secondary Dicarboxamides

Abstract: The synthesis and X-ray crystal structures of triptycene-derived secondary dicarboxamides 1 and 4-7 and reference compounds 2, 3, and 8 are reported. For comparison, molecular conformations of 1-8 in the gas phase and those of 1 and 3-6 in CD2Cl2 investigated by AM1 modeling and 1H NMR spectroscopy, respectively, are also included. The solid-state conformations of 1 and 5-8 are folded and compact, resulting from the cooperative effects of intramolecular amide-amide hydrogen bonding and edge-to-face arene-arene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…[20] This 3D-shape-persistent structure has several interesting applications in the field of: 1) molecular machines (e.g., gyroscopes, compasses, [21] brakes, [22] or ratchets [23] ), due to restricted rotation of the molecule preventing interdigitation; 2) molecular balances [24] for evaluation of p-p and other non-covalent interactions; 3) material sciences, such as polymers and liquid crystals for large internal free volumes providing large porosity for gas absorption; [25] and 4) crystal engineering in host-guest supramolecular chemistry. [26] The rigid triptycene core also has applications in coordination chemistry, catalysis for stabilizing highly reactive intermediates [27] and sterically bent complexes, [28] and electrophosphorescence. [29] Furthermore, electron and energy transfer in rigid triptycene-bipyridine metal complexes [30] and in porphyrin-based dyads and triads for charge separation [31] has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[20] This 3D-shape-persistent structure has several interesting applications in the field of: 1) molecular machines (e.g., gyroscopes, compasses, [21] brakes, [22] or ratchets [23] ), due to restricted rotation of the molecule preventing interdigitation; 2) molecular balances [24] for evaluation of p-p and other non-covalent interactions; 3) material sciences, such as polymers and liquid crystals for large internal free volumes providing large porosity for gas absorption; [25] and 4) crystal engineering in host-guest supramolecular chemistry. [26] The rigid triptycene core also has applications in coordination chemistry, catalysis for stabilizing highly reactive intermediates [27] and sterically bent complexes, [28] and electrophosphorescence. [29] Furthermore, electron and energy transfer in rigid triptycene-bipyridine metal complexes [30] and in porphyrin-based dyads and triads for charge separation [31] has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A number of single-crystal X-ray structures of triptycene derivatives have been solved since the first crystal structure analysis of unsubstituted triptycene by Anzenhofer and de Boer in 1970. [34,[37][38][39][40][41] Konarev et al and Veen et al reported the crystal structures of complexes formed between triptycene and C 60 . [30,31] In their work it can be seen that the concave face of triptycene is a good host for C 60 in a supramolecular host-guest system.…”
Section: X-ray Structuresmentioning
confidence: 99%
“…[10] Iptycenes are extensively employed in various applications because of their specific three dimensional scaffold in which arene rings are held together with a bicyclo [2.2.2]octane central unit. [11,12] In cases iptycene units are used in conjugated polymers, such polymers show high stability and amplified fluorescent character playing a crucial role as a sensor for nitroaromatic explosives at gaseous phase. [13] Iptycenes are also utilized to produce low dielectric constant polymeric materials having improved thermal stability and high T g .…”
Section: Introductionmentioning
confidence: 99%